Arctic shipping – a comparison study of northern sea route and northwest passage - Yen, Tingen. (2013)
The Arctic, with the lowest recorded temperature at -67.8ºC, is one of the iciest regions in the world. With its most distinguishable feature of sea-ice cover, the Arctic region has mostly remained unexplored and much less for shipping activities over the past decades.